Investigating Students Characteristics and Gender Differences Based on Multiple Intelligences Tendency - Samsudin R. Ishak; Rasuna Talib; Suleman Bouti (Ideas Publishing, 2022)
Students various characteristics need to be identified and facilitated at the first year in junior high school to determine their learning preferences and difficulties. This study aims to investigate: (i) students characteristics based on their multiple intelligences (MI) tendency; (ii) gender differences on their MI tendency. The study was held on twenty-seven students of grade seven (eight males and 19 females) at SMP Negeri 4 Randangan Satu Atap in 2021-2022 academic year by using one-shot descriptive survey method. The MI inventory result showed that interpersonal intelligence was strongly developed and the other seven intelligence were developed. Demographic background was contributing to the dominance of the three intelligences (interpersonal, naturalist, and verbal linguistics) as these three types of intelligence become the foundation of how these students who come from families of farmers, fishermen, and small traders living in rural area solve problems and produce works to live their daily lives. Even though the Kruskal-Wallis test showed no gender differences in all the eight intelligences, the item analysis showed that female and male respondents are different in 23 items. Males showed more interest in more expressive, active, and analytic activities, while females are better in items related to self-regulation. The information from MI Inventory can be an initial data for English teacher to decide which activities to include as learning input to match with students preferences. It is the first phase of need analysis to develop such an MI-based student-centred learning. Keragaman karakteristik siswa perlu diidentifikasi dan difasilitasi pada tahun pertama di sekolah menengah pertama untuk menentukan preferensi dan kesulitan belajar mereka. Penelitian ini bertujuan untuk menyelidiki: (i) karakteristik siswa berdasarkan kecenderungan kecerdasan majemuk (MI) mereka; (ii) perbedaan gender pada kecenderungan MI mereka. Penelitian dilaksanakan pada dua puluh tujuh siswa kelas tujuh (delapan laki-laki dan 19 perempuan) di SMP Negeri 4 Randangan Satu Atap pada tahun ajaran 2021-2022 dengan menggunakan metode survei deskriptif sekali tembak. Hasil MI Inventory menunjukkan bahwa kecerdasan interpersonal sangat berkembang dan tujuh kecerdasan lainnya pada level berkembang. Latar belakang demografis berkontribusi dalam dominasi tiga kecerdasan (interpersonal, naturalis, dan linguistik verbal) karena ketiga jenis kecerdasan ini menjadi dasar bagaimana para siswa yang berasal dari keluarga petani, nelayan, dan pedagang kecil yang tinggal di daerah pedesaan memecahkan masalah dan menghasilkan karya untuk menjalani kehidupan sehari-hari mereka. Meskipun tes Kruskal-Wallis tidak menunjukkan perbedaan gender dalam kedelapan kecerdasan tersebut, analisis item menunjukkan bahwa responden perempuan dan laki-laki berbeda dalam 23 item. Laki-laki menunjukkan lebih banyak minat pada kegiatan yang lebih ekspresif, aktif, dan analitik, sementara perempuan lebih baik dalam hal-hal yang berkaitan dengan pengaturan diri. Informasi dari MI Inventory dapat menjadi data awal bagi guru bahasa Inggris untuk memutuskan kegiatan mana yang akan dimasukkan sebagai input pembelajaran agar sesuai dengan preferensi siswa. Ini adalah fase pertama analisis kebutuhan untuk mengembangkan pembelajaran yang berpusat pada siswa berbasis MI.